2019
DOI: 10.26442/00403660.2019.01.000028
|View full text |Cite
|
Sign up to set email alerts
|

Levels of depression and life exhaustion in the open population of the middle urbanized Siberian city: gender differences

Abstract: The aim of the study was to determine the levels of depression and life exhaustion in men and women of the open urban population in the age range. Materials and methods. A single-stage epidemiological study was conducted among people of both sexes aged 25-64 in Tyumen. A representative sample was formed from the electoral lists of citizens by the method of "random numbers" - 2000 men and women with a response among men 85.0%, among women - 70.3%. The study of depression was conducted according to the algorithm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
(12 reference statements)
1
1
0
Order By: Relevance
“…The results of our study suggested that over 25% of surveyed men had a medium VE level, while every tenth study subject had a critically high VE value. Our findings partially agree with the results of the study conducted in Siberia on Tyumen men in terms of the critical VE level (12.3%), but are lower than the fraction of Tyumen males with a medium VE level (38.6%) [ 23 ], and are even lower than the level of corresponding indicators revealed by some studies conducted in Europe, where the proportion of men with a medium VE level was 51.7% and with a critical high VE level was 31.5% [ 24 ]. The lower prevalence of VE in the Moscow area, as compared to the Tyumen region, may have been caused by the higher quality of life in Muscovites and more severe climatic conditions in the Siberian region.…”
Section: Discussionsupporting
confidence: 91%
“…The results of our study suggested that over 25% of surveyed men had a medium VE level, while every tenth study subject had a critically high VE value. Our findings partially agree with the results of the study conducted in Siberia on Tyumen men in terms of the critical VE level (12.3%), but are lower than the fraction of Tyumen males with a medium VE level (38.6%) [ 23 ], and are even lower than the level of corresponding indicators revealed by some studies conducted in Europe, where the proportion of men with a medium VE level was 51.7% and with a critical high VE level was 31.5% [ 24 ]. The lower prevalence of VE in the Moscow area, as compared to the Tyumen region, may have been caused by the higher quality of life in Muscovites and more severe climatic conditions in the Siberian region.…”
Section: Discussionsupporting
confidence: 91%
“…37 Young women often experience high levels of daily stress due to the dual burden of family and home chores and job performance and are vulnerable to depression and anxiety symptoms. 38 , 39 To escape negative experiences of everyday life, they tend to emerge in intensive SMU. 40 Online discussions on platforms such as VKontakte (VK)—one of the most popular SM platforms in Russia 41 —or the uploading and watching of photos and short videos on Instagram and TikTok allow Russian users to forget their offline world obligations and problems at least temporarily.…”
Section: Introductionmentioning
confidence: 99%